2023
DOI: 10.3390/healthcare11142019
|View full text |Cite
|
Sign up to set email alerts
|

Information-Driven Integrated Healthcare: An Analysis of the Cooperation Strategy of County Medical Community Based on Multi-Subject Simulation

Abstract: The fragmentation and uneven quality of primary medical resources in China call for a deepening of integrated healthcare reform. China is promoting its county medical community (CMC) reform on a large scale in county-level administrative regions to promote the integration of local primary healthcare systems through information technology, which is consistent with the current trend of the digital governance era. Considering that the construction of a county medical community involves collaborative relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(62 reference statements)
1
0
0
Order By: Relevance
“…The revenue proportion of leading public hospitals decreased from 63.42 to 60.16%, and that of leading private hospitals decreased from 37.90 to 34.93%. Concurrently, there was an observed increase in the proportion of member hospitals, aligning with patterns identified in previous research [ 42 ]. It indicated that the MAs reform has effectively improved the capacity of member hospitals through sinking leading hospitals’ resources, which further guaranteed the balanced distribution of high-quality resources and the fairness of services.…”
Section: Discussionsupporting
confidence: 88%
“…The revenue proportion of leading public hospitals decreased from 63.42 to 60.16%, and that of leading private hospitals decreased from 37.90 to 34.93%. Concurrently, there was an observed increase in the proportion of member hospitals, aligning with patterns identified in previous research [ 42 ]. It indicated that the MAs reform has effectively improved the capacity of member hospitals through sinking leading hospitals’ resources, which further guaranteed the balanced distribution of high-quality resources and the fairness of services.…”
Section: Discussionsupporting
confidence: 88%